2023
DOI: 10.2172/1960692
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Manufacturing and Materials for Hydropower: Challenges and Opportunities

Abstract: Manufactured Components of Pressurized Conduits, Gates, and Valves ..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Research has shown that hydropower offers some of the lowest-cost electricity available. This affordability makes it an attractive choice for both developed and developing countries, particularly in the context of energy security and affordability concerns (Musa et al, 2023).…”
Section: Electricity Revenuesmentioning
confidence: 99%
“…Research has shown that hydropower offers some of the lowest-cost electricity available. This affordability makes it an attractive choice for both developed and developing countries, particularly in the context of energy security and affordability concerns (Musa et al, 2023).…”
Section: Electricity Revenuesmentioning
confidence: 99%
“…Mousavimehr, Yamini, and Kavianpour (2021) investigated shockwave effects and proposed experimental methods to mitigate them, recognizing AM's potential in fluid flow research. AM's established role in experimental fluid flow research, reviewed by Musa et al (2023), underlines its significance and potential advancements in various areas.…”
Section: Introductionmentioning
confidence: 99%